An Error Analysis on The Use of Simple Present Tense in The Descriptive Text Example - Sepriandi, Deni; Rachmijati, Cynantia (PROJECT (Professional Journal of English Education), 2025)
This research aims to analyze a mistake in the usage of simple present tense contained in the several descriptive texts which was taken from the British blog course, to find out which errors that are mostly found in the text and to find out how often the use of simple present tense in the text. The data were taken from 10 examples of descriptive texts written in the British blog. The method used by the researchers is descriptive qualitative. From the whole data, the researchers concluded that three types of errors were found in the data, which are omission, addition and misformation. Omission type found in 18 clauses (60%), addition type found in 3 clauses (10%), and misformation type found in 9 clauses (30%). The only type which is not occurred in the data was the misordering type. Meanwhile omission type found as the most dominant error types which occurred in the data. From the results above, it can be concluded that the texts in the blog is good because it has few errors. That means that the texts in the blog are good for use in learning.